Absence of sex differences in digit ratio in nestlings of the White Stork Ciconia ciconia, a monomorphic bird species. Issue 4 (2nd October 2019) - Kazimirski, Piotr P.; Kaczmarski, Mikołaj; Zagalska-Neubauer, Magdalena M.; Żołnierowicz, Katarzyna M.; Tobółka, Marcin
ABSTRACT: Capsule: There were no statistically significant differences in digit ratio between male and female chicks of the White Stork Ciconia ciconia . Aims: To test the hypothesis that the ratio of digit lengths was related to sex in White Stork nestlings, and to explore the relationship between digit ratio and other biometrics. Methods: We examined 101 White Stork chicks from a breeding population in western Poland. We measured the second, third and fourth digits from the left and right feet, took measurements of several body parameters (lengths of the bill and wing, body mass), and sexed all nestlings using molecular genetic methods. Results: Males were characterized by having significantly longer digits than females, however, we found no sexual dimorphism in any digit ratio in White Stork chicks. Nor did we find any relationship between digit ratio and body condition measurements. Conclusion: Our results confirm the hypothesis that sexual dimorphism for digit ratio does not occur in the sexually monomorphic White Stork.